About some shortcomings of the existing criminal legislation. (Journal of actual problems of jurisprudence, 2016)
In this article problems of law-making activity are considered. Shortcomings revealed in law-enforcement activity are analyzed. The author made an attempt to analyse shortcomings of legislative equipment. Recommendations about further improvement of the criminal legislation are offered.
Keywords: law-making; criminal policy; law-enforcement activity; equipment of lawmaking; estimated categories